2018
DOI: 10.4103/ua.ua_68_17
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of bacterial uropathogens and their susceptibility pattern: A 4-year (2013–2016) study from Aseer region, Saudi Arabia

Abstract: Purpose:To analyze the prevalence and resistance rates of bacterial agents causing urinary tract infections (UTIs) in Aseer, Saudi Arabia (2013–2016).Patients and Methods:This was a 4-year (2013–2016) retrospective study undertaken in Aseer Central Hospital, Saudi Arabia. A total of 49,779 urine and other UT specimens obtained from patients suspected of having a UTI were analyzed. Urine specimens were inoculated onto cystine lactose electrolyte deficient agar following standard procedures. Cultures showing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…However, in the case of linezolid, daptomycin, and vancomycin the resistances were the lowest. These findings are consistent with earlier reports and these drugs were recommended as revised empirical treatment for UTIs with continuous surveillance of uropathogens [71].…”
Section: Discussionsupporting
confidence: 93%
“…However, in the case of linezolid, daptomycin, and vancomycin the resistances were the lowest. These findings are consistent with earlier reports and these drugs were recommended as revised empirical treatment for UTIs with continuous surveillance of uropathogens [71].…”
Section: Discussionsupporting
confidence: 93%
“…The age group most affected by these urinary tract infections was 46 -60 years with 23.33%. This result was consistent with those reported in other countries of the world [27]. The female sex was the most affected by enterobacterial urinary tract infections with 51.07% against 48.97% for the male sex.…”
Section: Discussionsupporting
confidence: 92%
“…13 Another study by Alamri et al also support the results of current study by reporting that fosfomycin, nitrofurantoin and pivmecillinam can be the first line management options for treating uncomplicated UTIs. 17 Hence, ceftolozane/tazobactam are the approved antibacterial for empirical treatment of UTI and pyelonephritis in adults. 17,18 Many relevant studies and trials have concluded that fosfomycin and Nitrofurantoin are still the magic bullets to treat any type of UTI.…”
Section: Discussionmentioning
confidence: 99%
“…17 Hence, ceftolozane/tazobactam are the approved antibacterial for empirical treatment of UTI and pyelonephritis in adults. 17,18 Many relevant studies and trials have concluded that fosfomycin and Nitrofurantoin are still the magic bullets to treat any type of UTI. 19,20 With Fosfomycin found to be the most reliable option for managing any type of UTI, whether complicated or non-complicated.…”
Section: Discussionmentioning
confidence: 99%